Loss of CDX-2 expression is an independent poor prognostic biomarker in patients with early-stage deficient mismatch repair colorectal cancer - Korphaisarn K. (2023)
Aim: To investigate the clinicopathological factors, molecular features, and prognostic implications associated with loss of Caudal-related homeobox transcription factor 2 (CDX-2) expression in colorectal cancer (CRC) patients. Methods: Immunohistochemistry for CDX-2 expression was performed on formalin-fixed, paraffin-embedded primary CRC tissue samples from 449 patients. Correlation between CDX-2 expression and clinicopathological and molecular characteristics was evaluated. Univariate and multivariate survival analyses were performed to determine the prognostic value of loss of CDX-2 expression. Results: Of 449 patients, 84% were stage I–III. CDX-2-negative expression was identified in 18 of 441 (4.1%) patients. Loss of CDX-2 expression was more commonly found in patients with right-sided tumors rather than left-sided tumors (odds ratio [OR] = 3.57; p = 0.009), deficient mismatch repair (dMMR) compared to proficient MMR (pMMR) (OR = 3.7; p = 0.012), and BRAF mutation compared to BRAF wild type (OR = 8.06; p = 0.002). Univariate analysis revealed that stage I–III CRC patients with loss of CDX-2 expression had significantly worse overall survival (OS) and disease-free survival (DFS) than those with positive CDX-2 expression (5-year OS = 33.3% vs. 74.6%, respectively; p < 0.001, and 5-year DFS: 42.9% vs. 69.5%, respectively; p = 0.004). Loss of CDX-2 expression remained significantly associated with worse OS compared to positive CDX-2 expression in multivariate analysis (hazard ratio [HR] = 2.4; 95% confidence interval [CI], 1.12–5.11; p = 0.023). Conclusions: Loss of CDX-2 expression was found to be associated with right-sided tumor, dMMR status, and BRAF mutation. Moreover, loss of CDX-2 expression is a poor prognostic factor for OS in stage I–III, even among patients with dMMR tumors.